2000
DOI: 10.1034/j.1398-9995.2000.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation in asthma and perennial allergic rhinitis. Relationship with nonspecific bronchial responsiveness and maximal airway narrowing

Abstract: Induced sputum is an accurate method to study bronchial inflammation, allowing one to distinguish between rhinitis patients and mildly asthmatic patients. The fact that no relationship was detected between sputum inflammation and BHR suggests that other factors, such as airway remodeling, may be at least partly responsible for BHR in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 26 publications
(54 reference statements)
7
63
3
6
Order By: Relevance
“…Nevertheless, the accumulating evidence indicates that the pathophysiology is different between CVA and bronchial asthma. The most fundamental physiologic feature is a heightened cough response to methacholine-induced broncho-constriction in CVA, while this response is rather reduced in bronchial asthma 9 . The sensitivity of cough receptors located in the superficial layer of the airway wall is normal in CVA as well as bronchial asthma, but heightened in atopic cough.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the accumulating evidence indicates that the pathophysiology is different between CVA and bronchial asthma. The most fundamental physiologic feature is a heightened cough response to methacholine-induced broncho-constriction in CVA, while this response is rather reduced in bronchial asthma 9 . The sensitivity of cough receptors located in the superficial layer of the airway wall is normal in CVA as well as bronchial asthma, but heightened in atopic cough.…”
Section: Discussionmentioning
confidence: 99%
“…In this current study, study patients is divided into two category on the basis of the eosinophil count in sputum as follows, sputum eosinophil count >3%, and ≤ 3% category, it was observed that 90.0% populations had sputum eosinophil count >3% and 10% had ≤ 3% sputum eosinophil count. Alvarez et al 6 have reported that an increase of eosinophil count (>3.2%) in induced sputum has been observed in three out of six patients with chronic cough and bronchial hyperresponsiveness, who might be given a diagnosis of CVA 5 . Ayik et al 2 mentioned that sputum eosinophilia greater than 3.0% is present in 33.3% patients and the patients have been diagnosed as eosinophilic bronchitis.…”
Section: Sputum Eosinophilmentioning
confidence: 99%
“…It has been considered a precursor 3 and a variant form of classic asthma with typical symptoms of wheezing and dyspnea 4 . Several studies have examined mechanistic differences between CVA and classic asthma [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Sputum samples, obtained from HS and mannitol, were processed as described 11,12 and blindly evaluated. Samples were deemed adequate for cytological analysis when macrophages were observed and squamous cell contamination was under 20%.…”
Section: Sputum Analysismentioning
confidence: 99%